2013
DOI: 10.1002/adsc.201300416
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide Nanoparticles Supported on Graphene Oxide‐ Catalyzed S‐Arylation: An Efficient and Ligand‐Free Synthesis of Aryl Sulfides

Abstract: Copper oxide nanoparticles that are supported on graphene oxide as a catalytic system have been utilized for ligand‐free and solvent‐free CS cross‐coupling reactions with weak bases such as triethylamine. Symmetrical/unsymmetrical aryl sulfides have been synthesized by the coupling of different aryl halides with aromatic as well as aliphatic sulfides. Surprisingly, aryl chlorides also well reacted with different types of sulfides in the presence of dimethyl sulfoxide and cesium carbonate. Besides, this cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…The results showed that the N-doped Cu catalyst has good stability in the formic acid decomposition even at 478 K for at least 7 h on-stream and a significantly higher catalytic activity. Kamal et al [64] prepared GO-based nanocomposite (CuO@GO), and it was utilized for ligandfree and solvent-free C▬N and C▬S cross-coupling reactions with weak bases such as triethylamine (Scheme 10). They found that the CuO@GO is a simple and efficient catalyst for solvent-and ligand-free C▬S cross-coupling reactions in the presence of weak bases and relatively mild reaction conditions by using the CuO@GO catalytic system.…”
Section: Non-noble Metal Supported Carbon Nanocompositesmentioning
confidence: 99%
“…The results showed that the N-doped Cu catalyst has good stability in the formic acid decomposition even at 478 K for at least 7 h on-stream and a significantly higher catalytic activity. Kamal et al [64] prepared GO-based nanocomposite (CuO@GO), and it was utilized for ligandfree and solvent-free C▬N and C▬S cross-coupling reactions with weak bases such as triethylamine (Scheme 10). They found that the CuO@GO is a simple and efficient catalyst for solvent-and ligand-free C▬S cross-coupling reactions in the presence of weak bases and relatively mild reaction conditions by using the CuO@GO catalytic system.…”
Section: Non-noble Metal Supported Carbon Nanocompositesmentioning
confidence: 99%
“…So many works has been done on Graphene based materials, Graphene oxide based materials and metal oxide nanoparticles, but few works has been done on Graphene oxide-metal oxide mixed nanocomposites. For example, Ahmed Kamal et al reported that Copper Oxide-Graphene Oxide mixed nanoparticles acts as a catalyst in synthesis of ligand free Aryl sulphides [34].In another work; GO based CuO NPs composite electrode is used for highly enhanced non enzymatic glucose detection [35].…”
Section: Application Of Go-metal Oxide Mixed Nanocompositesmentioning
confidence: 99%
“…antimicrobial agents in coating/paints [87,88], healthcare [89], energy storage [90], chemical sensors [91], catalysts [92], and so on. Similar to Ag-NPs, the exact antimicrobial mechanism by which Cu-NPs exhibit its biocidal effects is still unclear [89].…”
Section: Copper Based Nanocomposite Membranes (Cu-nps)mentioning
confidence: 99%